Melissa officinalis essential oil modulates oxidative balance, cholinergic activity, and cognitive performance in a scopolamine-induced zebrafish model: implications for neuroprotective strategies in cognitive disorders - Brinza, Ion; Boiangiu, Razvan Stefan; Bagci, Eyup; Todirascu-Ciornea, Elena; Hritcu, Lucian; Dumitru, Gabriela (Nature Portfolio, 2025)
Melissa officinalis essential oil (MEO) possesses documented neuroprotective, antioxidant, and anxiolytic properties. This study investigated the effects of MEO (150 and 300 mu L/L) in a scopolamine (SCO, 100 mu M)-induced zebrafish model of cognitive impairment. Cognitive performance was assessed using the Y-maze and novel object recognition (NOR) tests for spatial and recognition memory. At the same time, anxiety-like behaviors were evaluated via the novel tank diving test (NTT) and the novel approach test (NAT). MEO was administered daily for 21 days, whereas SCO and the reference drug galantamine (GAL, 1 mg/L) were administered acutely before behavioral testing. MEO significantly ameliorated SCO-induced cognitive deficits, reduced anxiety-like behaviors, inhibited brain acetylcholinesterase (AChE) activity, and mitigated oxidative stress markers. In silico ADMET predictions for MEO's major constituents (citral, beta-caryophyllene, limonene, and alpha-pinene) indicated high gastrointestinal absorption, blood-brain barrier permeability, and favorable safety profiles, with no predicted mutagenic or hepatotoxic effects. Collectively, these findings support the neuroprotective and anxiolytic potential of MEO in a zebrafish model of cognitive dysfunction and suggest its promise as a candidate for further investigation in neurodegenerative disease research.
Keywords: Induced Memory Impairment; Alzheimers-Disease; Beta Peptide; Leaf Extract; Stress; L.; Anxiety; Tissues; Systems; Future